EFEKTIVITAS DAN EFISIENSI PENGGUNAAN SISTEM E-OFFICE DALAM KEGIATAN KORESPONDENSI PADA PT PENGEMBANGAN PARIWISATA INDONESIA (PERSERO) - Ardiyanti, Ni Nyoman Sri; Artatanaya, I Gusti Lanang Suta; Adnyana, Ida Bagus Artha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine the effectiveness and efficiency of using the e-office system in correspondence activities at PT Pengembangan Pariwisata Indonesia (Persero) The Nusa Dua Bali based on the characteristics of ISO/IEC 25010 : 2011 Quality in Use Model. The location of this research is at PT Indonesia Tourism Development (Persero)/ITDC The Nusa Dua. The number of samples used was 39 people using the census method. Collecting data using a 5 point likert scale questionnaire in the form of a google form. The data analysis technique used quantitative descriptive. The results showed the level of effectiveness of the use of the e-office system in correspondence activities at PT Pembangunan Wisata Indonesia (Persero) The Nusa Dua Bali with effective criteria. The efficiency level of using the e-office system in correspondence activities at PT Pembangunan Wisata Indonesia (Persero) The Nusa Dua Bali with efficient criteria. needs to be improved so that the implementation of e-office is more effective and efficient, namely the stability of the internet network to be maintained, the system to be updated and developed regularly, such as adding a digital signature feature, increasing file upload size, and being integrated directly with employee e-mails.